2004
DOI: 10.1093/ps/83.3.474
|View full text |Cite
|
Sign up to set email alerts
|

Low Feed Efficient Broilers Within a Single Genetic Line Exhibit Higher Oxidative Stress and Protein Expression in Breast Muscle with Lower Mitochondrial Complex Activity

Abstract: The objectives of this study were to determine the effects of low or high feed efficiency (FE) on a) protein oxidation, b) the activities of various respiratory chain complexes, and c) expression of various mitochondrial proteins in male broilers within a single genetic line. Tissue homogenate or mitochondria were isolated from breast muscle of broilers with high (0.80 +/- 0.01) and low FE (0.62 +/- 0.02). The complex activities were measured spectrophotometrically, and the levels of oxidized protein (carbonyl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
74
2
1

Year Published

2006
2006
2016
2016

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 112 publications
(87 citation statements)
references
References 76 publications
6
74
2
1
Order By: Relevance
“…Breast muscle mitochondria as well as gut, leg, heart, liver, and lymphocyte homogenates from low FE birds consistently exhibit a greater pervasive total protein carbonyl content compared with high FE birds (Bottje and Carstens, 2009). This supports previous observations of greater mitochondrial ROS production in low FE broilers (Bottje et al, 2002;Iqbal et al, 2004;OjanoDirain et al, 2005OjanoDirain et al, , 2007Lassiter et al, 2006) and in our high RFI pig lines (Grubbs et al, 2013a). This is further supported by low FE steers having greater neck muscle mitochondria protein carbonyl content (Sandelin, 2005).…”
Section: Methodssupporting
confidence: 91%
“…Breast muscle mitochondria as well as gut, leg, heart, liver, and lymphocyte homogenates from low FE birds consistently exhibit a greater pervasive total protein carbonyl content compared with high FE birds (Bottje and Carstens, 2009). This supports previous observations of greater mitochondrial ROS production in low FE broilers (Bottje et al, 2002;Iqbal et al, 2004;OjanoDirain et al, 2005OjanoDirain et al, , 2007Lassiter et al, 2006) and in our high RFI pig lines (Grubbs et al, 2013a). This is further supported by low FE steers having greater neck muscle mitochondria protein carbonyl content (Sandelin, 2005).…”
Section: Methodssupporting
confidence: 91%
“…CYTB is an essential subunit of the functional center of the ubiquinol-cytochrome-c reductase complex (complex III) and catalyzes the transfer of electrons from ubiquinol to cytochrome c (Yu et al, 1999). Therefore, it has been widely used to evaluate mitochondrial activity (Carper et al, 1999;Iqbal et al, 2004). In addition, we also observed reduced expression of the ATP6 gene in heat stressed pigs from phase 2, irrespective of dietary aP levels ( Figure 1).…”
Section: Discussionsupporting
confidence: 59%
“…Birds receiving feed supplemented with 12% glycerol showed higher COX III expression and worse feed efficiency than birds receiving no glycerol and 8% glycerol. Similar to this finding, other studies have found increased expression of COX III in birds with poor feed efficiency (Iqbal et al, 2004;Iqbal et al, 2005;Lassiter et al, 2006;Tinsley et al, 2010), suggesting that there is a relationship between poor feed efficiency and increased COX III expression.…”
Section: Discussionsupporting
confidence: 87%
“…According to Iqbal et al (2004), although the exact mechanism of action of COX III has not yet been fully determined, the high expression of COX III in low feed efficiency birds could represent a compensatory response against possible oxidative stress caused by enhanced protein oxidation. The increase in COX III expression in animals fed a diet containing 12% glycerol is a strong indication of the likely increase in reactive oxygen species caused by diet, since the function of COX III is more closely linked to stress oxidative responses and activities relating to changes in proton position (You et al, 2002).…”
Section: Discussionmentioning
confidence: 99%